Convergence of Service Providers and Managers’ Perspectives on Strengths, Gaps, and Priorities for Rural Health System Redesign: A Whole-Systems Qualitative Study in Washington County, Maine - Rebecca L. West (Journal of Primary Care & Community Health, 2022)
Introduction: Both rural residents and state government leaders describe a need to redesign rural health care systems. Community members should be at the center of this effort. Methods: We conducted 46 in-depth interviews of direct service providers between September and November 2020 in Washington County, Maine. Data were analyzed using a thematic analysis approach. Results: Existing strengths included collaboration between government and health systems, and community-based services. Gaps included insufficient workforce, restricted scope of licensing and poor reimbursement, lack of coordination between health systems, and limited paramedicine capacity. Strategies for health system redesign included addressing maldistribution of services and resource optimization, changing federal and state legislation around insurance and scope of practice, and moving toward value-based purchasing models. Conclusions: Participants provided pragmatic recommendations based on their deep understanding of the community context. Lessons learned are likely to be salient in areas with similar profiles regarding rurality and poverty.